C. F. Lehmann-Haupt's Studies on Assyrian Inscriptions of the Armenian Highland - Vahe Sargsyan (Banber Arevelagitut'yan Instituti)
Prominent German orientalist C. F. Lehmann-Haupt explored the Tigris Tunnel during his travels in the Armenian Highland and Northern Mesopotamia from 1898 to 1899.1 According to him, the kings of Assyria considered this place as the source of the Tigris (or at least one of its sources) and tried to reach it during their campaigns. This was probably conditioned by the circumstance that the waters of the Tigris River, which “flooded the walls” of the Assyrian capitals of Assur, Calah and Nineveh, flowed through the rocks there. According to the inscriptions of the Tigris Tunnel, the sacrifices made by the Assyrian kings in honor of their gods were considered to be dedicated to the god of the river and the spring [9: A.0.102.6 ii 34-40; A.0.102.8: 20-23; A.0.102.14: 67-72; 14: 434].